Unity-Supported Game-Based Learning: Teachers' Perspectives on the Development of Classroom Management Skills - Karabatak, Songul; Kuloglu, Aysenur; Alanoglu, Maslim; Bozkurt, Ezgi (Institute of Electrical and Electronics Engineers Inc., 2025)
This study aims to examine teachers' perspectives on the use of Unity-supported game-based learning (USGBL) in developing classroom management skills among pre-service teachers. The research was conducted using a qualitative approach. A case study design was adopted, and a maximum variation sampling method was employed. In this context, the opinions of teachers from different subject areas were gathered. Data collection was carried out through semi-structured interviews, and the collected data was analyzed using content analysis. The findings of the study indicate that traditional teacher training methods are inadequate in developing classroom management skills, highlighting the need for innovative models. Participants emphasized that pre-service teachers should receive more hands-on training, as theoretical knowledge alone is insufficient in real classroom settings. They also stressed the necessity of integrating technology-supported alternative teaching methods into the training process. Additionally, it was found that game- and simulation-based education, such as Unity, positively contributes to student motivation and the learning process. Therefore, it was concluded that USGBL can support classroom management skills in four key areas: enhancing motivation and willingness to learn, improving self-confidence and self-efficacy, fostering quick decision-making and problem-solving skills, and developing digital competence and technology integration. These results demonstrate that USGBL is not merely an entertaining approach but also a tool that strengthens pedagogical competencies. It is recommended that practice-oriented reforms be implemented in education faculties and that programs be developed to better prepare pre-service teachers for real classroom environments.. © 2025 IEEE.
13th International Symposium on Digital Forensics and Security, ISDFS 2025 -- 24 April 2025 through 25 April 2025 -- Boston -- 209331
Keywords: Classroom Management Skills; Game Based Learning; Interactive Education Simulations; Unity